Leveraging mathematical methods for environmentally friendly waste management: Locating optimal facility sites - Aidoo, Emmanuel; Nandakumar, C D; Mwinkume, Gabriel; Raj, A. Bernick (Edelweiss Applied Science and Technology, 2025)
This study examines the Uncapacitated Facility Location Problem (UFLP) in the context of landfill placement, a critical factor in sustainable waste management. It introduces an enhanced model that integrates operational logistics, cost structures, demand distribution, temporal dynamics, and population growth projections to optimize landfill siting strategies. We apply the proposed model in a case study of Cape Coast Metropolis, Ghana, which includes twenty-three suburbs and seven potential landfill sites. The analysis evaluates the impact of landfill distribution on waste management efficiency and operational expenses over time. Results indicate that while increasing the number of landfills improves waste distribution, it also escalates long-term operational costs. The study underscores the need for strategic planning to balance efficiency and cost-effectiveness. Additionally, incorporating temporal dynamics is crucial for long-term sustainability. The study highlights the importance of integrating economic, operational, and environmental considerations in landfill siting decisions, providing a foundation for future research on sustainable waste management. Optimized landfill placement can lead to significant cost savings and improved resource allocation. The findings inform policymakers and businesses in developing regulations that promote efficient facility placement, enhance disaster response, and support long-term waste management sustainability.